The Effectiveness Of Islamic Banking Financing In Enhancing Economic Growth In Sumenep Regency - M. Johari, Sobar; Andrian Bungas, Ihzan (International Journal of Science, Technology & Management, 2025)
This study investigates the effectiveness of Islamic banking financing in enhancing economic growth in Sumenep Regency. Islamic banking plays a significant role in providing Sharia-compliant financing solutions, especially for Small and Medium Enterprises (SMEs) that form the backbone of the local economy. The research employs a mixed-methods approach combining quantitative and qualitative data collected from Islamic banking institutions and regional economic statistics between 2018 and 2023. Quantitative analysis utilizes multiple regression models to measure the impact of Islamic financing schemes, such as Mudharabah and Musyarakah, on the growth of SMEs and Gross Regional Domestic Product (GRDP) in Sumenep. Qualitative data from interviews with banking officials and SME entrepreneurs provide insights into factors that enhance financing effectiveness, including trust, compliance with Islamic economic principles, and accessibility of capital. The findings indicate that Islamic banking financing significantly contributes to economic growth by supporting SME development, improving income levels, and fostering sustainable business practices. However, challenges such as limited human resources and regulatory constraints are identified as barriers to maximizing financing potential. The study concludes that optimizing Islamic banking products and strengthening institutional support can further accelerate economic growth in the region. This research provides valuable implications for policymakers, banking institutions, and stakeholders seeking to leverage Islamic finance as a tool for regional economic development.